Examining the interplay of childhood abuse, bullying, and bullying victimization in middle school students: a serial mediation analysis - Bai, Ting; Lang, Min; Jin, Yue; Li, Jingyi; Chen, Peng (Frontiers in Psychology, 2025)
IntroductionChildhood abuse and bullying are youth problem worldwide, yet the detrimental effects of child abuse is underestimated in China. The aim of this study is to analyze the relationship between child abuse and bullying and victimization, and to explore the mediating roles of self-esteem, peer relationships, and moral disengagement in the chain between childhood abuse, school bullying, and victimization among junior high school.MethodsThis study included 1,327 adolescents (52.3% girls, 47.3% boys) from public schools in Sichuan Province, China. We conducted a cross-sectional questionnaire survey using the Child Trauma Scale-Short Form, Bullying Participatory Behavior Questionnaire, Self-Esteem Scale, Peer Relationships Scale, and the Moral Disengagement Questionnaire. The bootstrap technique was used to conduct mediation analysis. SPSS Process Macro 3.0 control prepared by Hayes, Gender and grade were used as the control variables in model 6.ResultsChildhood abuse significantly predicts both bullying (B =0.08, p < 0.001) and victimization (B =0.17, p < 0.001). Meanwhile, the serial mediating effect via self-esteem, peer relationships and moral disengagement between childhood abuse and bullying was 0.0015 (95% CI: 0.0003–0.0029), the serial mediating effect via self-esteem, peer relationships and moral disengagement between childhood abuse and bullying victimization was 0.0005 (95% CI: 0.0000–0.0014).DiscussionThe investigation into the chain mediating effects of self-esteem, peer relationships, and moral disengagement on the interconnections between childhood abuse, bullying, and bullying victimization has deepened our understanding of the cycles of violence and victimization. It has pointed out that family factors may be key elements in bullying prevention.